2015
DOI: 10.1007/978-3-319-16009-2_6
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 Enzymes in the Bioactivation of Polyunsaturated Fatty Acids and Their Role in Cardiovascular Disease

Abstract: Various members of the cytochrome P450 (CYP) superfamily have the capacity of metabolizing omega-6 and omega-3 polyunsaturated fatty acids (n-6 and n-3 PUFAs). In most mammalian tissues, CYP2C and CYP2J enzymes are the major PUFA epoxygenases, whereas CYP4A and CYP4F subfamily members function as PUFA hydroxylases. The individual CYP enzymes differ in their substrate specificities as well as regio- and stereoselectivities and thus produce distinct sets of epoxy and/or hydroxy metabolites, collectively termed C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 276 publications
3
54
0
Order By: Relevance
“…Recent studies provide strong evidence that P450 enzymes and their AA metabolites play differential roles in most cardiac diseases; some of these metabolites are cadiotoxic, others showed cardioprotective effects (Westphal et al, 2015;Zu et al, 2016). One group of AA metabolites that have not been fully studied with respect to cardiac hypertrophy is subterminal HETEs, specifically 16-, 17-, 18-, and 19-HETE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies provide strong evidence that P450 enzymes and their AA metabolites play differential roles in most cardiac diseases; some of these metabolites are cadiotoxic, others showed cardioprotective effects (Westphal et al, 2015;Zu et al, 2016). One group of AA metabolites that have not been fully studied with respect to cardiac hypertrophy is subterminal HETEs, specifically 16-, 17-, 18-, and 19-HETE.…”
Section: Discussionmentioning
confidence: 99%
“…For years, AA was thought to be solely metabolized by cyclo-oxygenase (COX) and lipoxygenase (LOX) enzymes via conversion of AA into prostaglandins and leukotrienes (LTs), respectively (Chandrasekharan et al, 2016). In the heart, discovery of a novel branch of AA metabolism through P450 enzymes led to special focus on the role of their biologically active metabolites in multiple heart diseases (Westphal et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, EPA treatment attenuated post‐MI cardiac remodeling. However, there is a growing body of evidence to suggest that the beneficial effects of EPA are due to the metabolites rather than the parent compound . For example, one study indicated that dietary enrichment with n‐3 fatty acids suppressed choroidal neovascularization, vascular leakage, and immune cell recruitment to the lesion site in a mouse model of laser‐induced choroidal neovascularization .…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a growing body of evidence to suggest that the beneficial effects of EPA are due to the metabolites rather than the parent compound. 46 For example, one study indicated that dietary enrichment with n-3 fatty acids suppressed choroidal neovascularization, vascular leakage, and immune cell recruitment to the lesion site in a mouse model of laser-induced choroidal neovascularization. 47 In this study, 17,18-epoxyeicosatetraenoic acid derived from EPA and 19,20-epoxydocosapentaenoic acid derived from docosahexaenoic acid, the major cytochrome P450 (CYP)-generated metabolites of these primary n-3 fatty acids, were identified as the key lipid mediators of disease resolution.…”
Section: Discussionmentioning
confidence: 99%
“…acting anti-inflammatory and vasodilatory [16] and are present in body fluids and tissues (e.g. plasma, red blood cells, liver, kidney, lung, heart) [17,18]. In mammals they are generated from enzymatic conversion of the naturally occurring all-cis PUFA by cytochrome P450 monooxygenases (CYP) leading to regioisomeric cis-epoxy-PUFA (R,S-and S,R-enantiomers, Fig.…”
Section: Cell Culture Assaymentioning
confidence: 99%